HEPATO-AND NEPHRO-PROTECTIVE EFFECTS OF METHANOL EXTRACT OF CITRULLUS LANATUS RIND IN WISTAR RATS FED WITH USED MOTOR ENGINE OIL CONTAMINATED FEED - Ebhohon, S. O.; Ibeh, R. C.; Ejiofor, U. E.; Abu, O. D.; Osegenna, S. C. (FUDMA JOURNAL OF SCIENCES, 2023)
The present study investigated the hepato- and nephroprotective effects of methanol extract of Citrullus lanatus rind in Wistar rats fed with used motor engine oil contaminated feed (UMEO). Twenty-five (25) adult male Wistar rats were randomly assigned to five groups of five rats each. One group served as normal control, the remaining groups were fed 4 ml UMEO/kg feed, 100 mg/kg body weight (bwt) of vitamin C, 250 mg/kg bwt of extract, and 500 mg/kg bwt of extract respectively. After 28 days of treatment, the rats were euthanized, and blood and kidney samples collected for biochemical analysis. Results showed that the oral LD50 of methanol extract of C. lanatus rind was greater than 5000 mg/kg bwt. Treatment with methanol extract of C. lanatus significantly (p< 0.05) reduced the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and concentration of total bilirubin. There were no significant differences in the concentrations of total protein (TP) and creatinine among the groups (p> 0.05). The concentration of urea was significantly (p< 0.05) increased in groups treated with the extract and vitamin C compared to the untreated animals. The activities of superoxide dismutase (SOD) and catalase were significantly reduced in negative control group compared to the control and treatment groups. Treatment with the extract significantly reduced UMEO -induced increase in malondialdehyde (MDA) concentration. The results of this study indicate that methanol extract of Citrullus lanatus rind may protects liver and kidney against injuries imposed by foreign compounds.
Keywords: Antioxidants, Citrullus lanatus, Kidney, Liver, Oxidative Stress